Chemically Stable Carbazole-Based Imine Covalent Organic Frameworks with Acidochromic Response for Humidity Control Applications - Gilmanova, Leisan; Bon, Volodymyr; Shupletsov, Leonid; Pohl, Darius; Rauche, Marcus; Brunner, Eike; Kaskel, Stefan (Journal of the American Chemical Society, 2021)
Isoreticular chemically stable two-dimensional imine covalent organic frameworks (COFs), further denoted as DUT-175 and DUT-176, are obtained in a reaction of 4,4′-bis(9H-carbazol-9-yl)biphenyl tetraaldehyde with phenyldiamine and benzidine. The crystal structures, solved and refined from the powder X-ray diffraction data and confirmed by high-resolution transmission electron microscopy, indicate AA-stacked layer structures. Both structures feature distorted hexagonal channel pores, assuring remarkable porosity (SBET = 1071 m2 g-1 for DUT-175 and SBET = 1062 m2 g-1 for DUT-176), as confirmed by adsorption of gases and vapors. The complex conjugated πsystem of the COFs involves electron-rich carbazole building units, which in combination with the imine groups allow reversible pH-dependent protonation of the frameworks, accompanied by charge transfer and shift of the absorption bands in the UV-vis spectrum. The sigmoidal shape of the water vapor adsorption and desorption isotherms with a steep adsorption step at p/p0 = 0.4-0.6 in combination with excellent stability over dozens of adsorption and desorption cycles ranks these COFs among the best materials for indoor humidity control applications.
CRIS-Team Scopus Importer:2022-04-14